SHIFT FROM BANK DEPOSITS TO INVESTMENTS IN INDIA: IMPLICATIONS FOR BANKING STABILITY - Mundhara , Rukmini (Indian Journal of Finance and Banking, 2025)
Over the last twenty years, the financial landscape of Indian households has undergone a significant transformation, characterized by a decline in dependence on traditional bank deposits and an increasing preference for market-oriented investment options. This shift reflects broader changes in financial behavior driven by macroeconomic factors, shifting consumer preferences, and advancements in financial technology. This study aims to explore the transition from traditional bank deposits to alternative investment opportunities in India and assess their impact on the liquidity and stability of the banking sector. By examining long-term trends, the research considers the determinants of this shift, including GDP growth, inflation, interest rates, financial literacy, and engagement with digital platforms. A mixed-methods approach is utilized, integrating quantitative analysis of secondary data sourced from the Reserve Bank of India (RBI), AMFI, and leading commercial banks, alongside qualitative insights drawn from existing literature and publicly accessible datasets. Analytical tools such as regression analysis, correlation metrics, and pivot tables are employed to investigate the relationships among macroeconomic indicators, deposit behaviors, and investment trends. The findings indicate a strong positive correlation between GDP and both deposits and investments. In contrast, financial literacy and digital engagement exhibit a significant inverse relationship with deposit preferences and a direct correlation with investment decisions. Additionally, regression analysis reveals that factors beyond traditional interest rates and banking metrics are increasingly influencing the growth of investments. These results highlight the evolving dynamics of household financial behavior in India and their long-term implications for deposit mobilization and the operational frameworks of commercial banks. JEL Classification Codes: G21, G41, E44.